Study of the Effect of Magnetic Abrasive Finishing on the Material Removal of AA1100 Aluminum Alloy - Majeed, Mariam; H.Khadum, Ali; Al-Zubaidi, Salah (Al-Khwarizmi Engineering Journal, 2023)
This study evaluates the performance of magnetic abrasive finishing (MAF) of aluminum alloy in terms of achieving materials removal (MR). A vertical milling machine is used to perform the finishing process using a developed MAF unit that consists of an inductor made out of a 150 mm long and 20 mm diameter iron core wound with 1500 turns and 0.5 mm copper wire. The commutator and magnetic pole are attached at the top and bottom of the inductor, respectively. The required current is supplied using a DC power supply. The South Pole workpiece is a 100×50×3 mm3 plate of AA 1100 aluminum alloy, whereas the magnetic pole represented the North Pole. Pole rotational speed, applied current, and abrasive finishing time was selected as input parameters of the MAF with three-level of (270, 600. 930 rpm; 0.5, 1, 1.5 Amp; 6,9,12 min). The L9 orthogonal array of the Taguchi method was utilized to examine the impact of each independent input. The obtained results clarify that applied current was the most effective factor in terms of its contribution (63.16%) in the produced MR, followed by time finishing and rotational speed.